Magnetic composites of CoFe2O4 nanoparticles in a poly(aniline) matrix: Enhancement of remanence ratio and coercivity - Antonel, Paula Soledad (2015)
Magnetic composites of cobalt ferrite nanoparticles and poly(aniline) have been synthesized in acid media and characterized by X-ray diffraction studies, scanning and transmission electron microscopy observation, thermogravimetric analysis, conductivity and infrared spectroscopy measurements. The magnetic behavior was studied through DC magnetization measurements; hysteresis loops were observed, showing ferromagnetic behavior for particles and composites. The remanence ratio increases as the polymer contents increases, the coercivity decreases first and then increases, and the saturation magnetization does not follow the ferrite mass fraction in the composite. It is proposed that an indirect exchange mechanism (RKKY-like) between the nanoparticles and PANI localized spins mediated by the conduction electrons is responsible for the observed magnetic behavior. The results suggest the presence of particle-matrix interactions related to the amount of polymer present, thus, in turn suggesting that the material magnetic properties could be controlled through the nanoparticles to polymer ratio.